OC-054 Development and Validation of a Classification System to Identify Barrett's Neoplasia Using Acetic Acid Chromoendoscopy: The Predict Classification. (17th August 2016) - Kandiah, K; Chedgy, FJQ; Longcroft-Wheaton, G; Pech, O; De Caestecker, J; Green, S; Gordon, C; Li, A; Barr, H; Bhandari, P; ,
Abstract : Introduction: Neoplasia in Barrett's can be discrete and patchy. Acetic acid chromoendoscopy (AAC) has been demonstrated to highlight neoplastic areas allowing for earlier treatment. Previous efforts to create a classification system for AAC have not been systematic and rigorous in their methodology. We aimed to develop and validate a classification system to identify Barrett's neoplasia using AAC. Methods: Three expert AAC endoscopists (PB, GLW, OP) formed a working group to identify AAC component criteria of non-dysplastic and dysplastic Barrett's using a modified Delphi Method. Following this, a panel of 7 AAC experienced endoscopists assessed the performance of each individual criterion by reviewing a bespoke online database of 40 images and 40 videos of non-dysplastic and dysplastic Barrett's lesions. Finally, we assessed the diagnostic reproducibility of the validated criteria by asking 13 non-AAC experienced endoscopists to complete an assessment tool of 40 images and 20 videos. Results: The component criteria identified by the expert AAC endoscopists were as follows Early focal loss of acetowhitening Present : Indicates the presence of neoplasia Absent: Indicates the absence of neoplasia Surface pattern Normal (Large uniformly distributed pits) : Indicates non-neoplastic Barrett's Abnormal (Compact, irregular or absent pits) : Indicates neoplastic Barrett's A total of 560 observations were undertaken to validate these criteria. The sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) are shown in Table 1 : When the AAC validated criteria are applied by the 13 endoscopists, the sensitivity, specificity, NPV and PPV of detecting neoplastic Barrett's are 98.5%, 64.0%, 97.5% and 72.5% respectively. Conclusion: We have developed and established the validity of a simple classification system to identify Barrett's neoplasia using AAC. When non-AAC experienced endoscopists apply these criteria, the sensitivity and NPV meet the recommended PIVI threshold. Disclosure of Interest: None Declared